(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, the existence of positive solutions of the following third-order three-point boundary value problem with p-Laplacian cases(φ_p(u''(t)))'+f(t,u(t))=0, t(0,1), u(0)=α u(η), u(1)=α u(η), u''(0)=0, casesis studied, where φ_p(s) = |s|^p−2 s, p > 1. By using the fixed point index method, we establish sufficient conditions for the existence of at least one or at least two positive solutions for the above boundary value problem. The main result is demonstrated by providing an example as an application.